Moisture Conservation Efficiency of Some Legumes and Their Effect on the Yield of Rabi (Brassica Juncea Coss) Under Rainfed Conditions - Bhatia, K S; Srivastava, K K; Lal, B (Annals of Arid Zone, 2016)
-Â